Optimising Noisy Objective Functions - Bulger, David W.; Romeijn, H. Edwin (Journal of global optimization, 2005)
This discussion paper considers the use of stochastic algorithms for solving global optimisation problems in which function evaluations are subject to random noise. An idea is outlined for discussion at the forthcoming Stochastic Global Optimisation 2001 workshop in Hanmer in June; we propose that a noisy version of pure random search be studied. [PUBLICATION ABSTRACT]